Free Radical Scavenging Activity and Cytoprotective Effect of Soybean Milk Fermented with Lactobacillus Fermentum Zhao. Issue 3 (16th November 2015) - Suo, Huayi; Qian, Yu; Feng, Xia; Wang, Hongwei; Zhao, Xin; Song, Jia‐Le
Abstract: The objective of this study was to investigate the in vitro free radical scavenging activity and protective effects of soymilk fermented by L actobacillus fermentum Zhao (FSM‐FLZ) in hydrogen peroxide (H2 O2 )‐induced porcine renal proximal tubule LLC‐PK1 cells. FSM‐FLZ was effective against DPPH and ● OH radical in a concentration‐dependent manner. FSM‐FLZ treatment significantly increased cell viability and reduced the H2 O2 ‐induced oxidative injury in LLC‐PK1 cells. In addition, FSM‐FLZ dose‐dependently decreased the intracellular reactive oxygen species (ROS) levels and lipid peroxidation, and increased the activities and mRNA expressions of endogenous catalase and superoxide dismutase enzymes. This study demonstrated that FSM‐FLZ is a free radical scavenger and protects against H2 O2 ‐induced oxidative injury in LLC‐PK1 cells through reducing intracellular ROS levels, inhibiting lipid peroxidation and increasing the antioxidant enzyme activity. Practical Applications: Lactic acid bacteria (LAB) are a well‐known probiotic and showed antimicrobial, antitumor, reduction of serum cholesterol and immune‐modulation activity. L actobacillus fermentum ZHAO is a newly discovered LAB; it was isolated from Yak yoghurt. It was used to ferment soybean milk and the antioxidation effects of soybean milk were determined. L . fermentum ZHAO fermented soybean milk could be used as a new functional food.